The Science of Scale for Violence Prevention: A New Agenda for Family Strengthening in Low- and Middle-Income Countries - Shenderovich, Yulia; Lachman, Jamie M.; Ward, Catherine L.; Wessels, Inge; Gardner, Frances; Tomlinson, Mark; Oliver, Daniel; Janowski, Roselinde; Martin, Mackenzie; Okop, Kufre; Sacolo-Gwebu, Hlengiwe; Ngcobo, Lindokuhle L.; et al. (Frontiers in Public Health, 2021)
Ending all violence against children by 2030 is a core part of Sustainable Development Goals 5 and 16. A number of promising violence reduction strategies have been identified in research studies. However, we lack an understanding of the implementation and impact of these programs in respect to their delivery at a large scale or within existing service systems, particularly in low- and middle-income countries (LMICs). We advocate for greater collaboration between researchers, policymakers, donors, governments, non-governmental organizations, and program managers and staff to study how violence prevention programs operate on a large scale. We describe a new initiative aiming to foster such collaborations in the field of family strengthening programs.